2020
DOI: 10.1038/s41598-020-63357-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal LXR Regulates Neuregulin 1 Expression and Sciatic Nerve-Associated Cell Signaling in Western Diet-fed Rodents

Abstract: Neuropathic pain caused by peripheral nerve injuries significantly affects sensory perception and quality of life. Accumulating evidence strongly link cholesterol with development and progression of Obesity and Diabetes associated-neuropathies. However, the exact mechanisms of how cholesterol/ lipid metabolism in peripheral nervous system (PNS) contributes to the pathogenesis of neuropathy remains poorly understood. Dysregulation of LXR pathways have been identified in many neuropathic models. The cholesterol … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…This improvement in pain indices was also accompanied with an increase in SBNP density suggesting LXRs activation either attenuated distal degeneration or stimulated nerve regeneration. This is consistent with our prior studies that showed LXR agonist treatment prevents progression of obesity-induced allodynia by altering peripheral sensory neuron function and their interaction with associated cells [ 10 , 62 ]. Peripheral macrophages have been implicated in the development of mechanical allodynia [ 63 ] and infiltration by immune cells happen differently in myelinated or non-myelinated fibers that may explain temporal differences in sensory behavior.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This improvement in pain indices was also accompanied with an increase in SBNP density suggesting LXRs activation either attenuated distal degeneration or stimulated nerve regeneration. This is consistent with our prior studies that showed LXR agonist treatment prevents progression of obesity-induced allodynia by altering peripheral sensory neuron function and their interaction with associated cells [ 10 , 62 ]. Peripheral macrophages have been implicated in the development of mechanical allodynia [ 63 ] and infiltration by immune cells happen differently in myelinated or non-myelinated fibers that may explain temporal differences in sensory behavior.…”
Section: Discussionsupporting
confidence: 93%
“…LXRs are oxidized cholesterol derivative ligand-activated transcription factors and consist of two isoforms LXRα and LXRβ [ 10 , 30 , 31 , 62 ]. LXRs play an important role in cholesterol metabolism [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore tested the hypothesis that activation of LXRs can be effective in delaying/improving the progression of and found that the LXR selective agonist GW3965 either reversed or delayed the progression of multiple indices of neuropathy. This is consistent with our prior studies that showed LXR agonist treatment prevents progression of obesity-induced allodynia by altering peripheral sensory neuron function and their interaction with associated cells [9, 43]. Our findings suggest that activation of LXRs may influence sensory perception of the aged mice via activation of LXRs in macrophages of the SN that induces the M2 phenotype involved in nerve regeneration.…”
Section: Discussionsupporting
confidence: 93%
“…LXRs are oxidized cholesterol derivative ligand-activated transcription factors and consist of two isoforms LXRα and LXRß [9, 24, 25, 43]. LXRs play an important role in cholesterol metabolism [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Gavini et al showed that the LXR reduces the proliferation of the Schwann cells in obesity. The effect was directly related to the downregulation of neurogenin 1 by saturated fatty acids [ 80 ]. The same group found also that activation of LXR can reduce pain in diet-induced obesity.…”
Section: Insulin Resistance Dyslipidemia Inflammatory and Oxidative M...mentioning
confidence: 99%